A National Institute of Neurological Disorders and Stroke (NINDS) Project: Traumatic Brain Injury v3.0 Clinical Common Data Element Recommendations - Giacino, Joseph; Dowd, Becky; Gay, Katelyn; Sheikh, Muniza; Mellick, Dave; Pape, Marcy; Awwad, Hibah; Umoh, Nsini (Archives of physical medicine and rehabilitation, 2025)
To update the National Institute of Neurological Disorders and Stroke (NINDS) Traumatic Brain Injury (TBI) Clinical Common Data Elements (CDEs) to v3.0. The purpose of CDEs is to accelerate data sharing, educate investigators, and increase study efficiency and data quality. CDE usage streamlines data harmonization and curation to make data findable, accessible, interoperable, and reusable in alignment with “Findability, Accessibility, Interoperability, and Reuse” data principles. Project goals are to reorganize and expand the existing domains while narrowing the CDE portfolio to provide more specific guidance on CDE selection, based on context of use. The 2012 TBI v2.0 CDEs will be comprehensively reviewed and updated to v3.0 based on peer-reviewed literature, CDE use metrics and secondary analysis of CDEs in the Federal Interagency Traumatic Brain Injury Research Informatics System, and improved categorization. In 2024, the NINDS will convene a subject-matter expert working group to develop updated template case report forms, data dictionaries, instrument informational documents, and guidance documents. A 2-tiered process for CDE selection will be implemented using a semiautomated NINDS vetting platform that will undergo beta-testing to ensure a systematic and consistent approach. First, instruments will be qualified as CDEs using operationally-defined criteria adapted and expanded from the PhenX Toolkit. Second, qualified CDEs will be evaluated within specific contexts of use using the Evidence-Based Clinical Outcomes Assessment Platform, which was developed for validation of TBI assessment measures with support from the Department of Defense. In version 3.0, TBI CDEs will encompass 10 construct domains and will be reclassified based on study type and strength of evidence. Classifications will include redefined Core and Supplemental – Highly Recommended CDEs, essential for all or specified study types, respectively, and Supplemental and Exploratory CDEs. The updated recommendations will be posted on the NINDS CDE website after public review. The NINDS CDEs are an evolving resource updated as research advances and best clinical practice measures are validated. NINDS encourages the use of TBI CDEs to standardize collection of research data across studies and facilitate comparison of findings, which can help establish a stronger evidence base for TBI management and recovery along the trajectory of care. The TBI v3.0 CDE initiative will improve the utility of CDEs as a valuable starting point for researchers, ultimately increasing congruency among the multiple disciplines that evaluate patients across various stages of TBI. none.